اسلام اور عیسائیت میں مشترک طریقہ عبادت کا تصور اور عصر حاضر میں اس کی صورتیں: تنقیدی اور تقابلی مطالعہ: The Concepts of Common Worship in Islam and Christianity and its forms in Contemporary era: A Critical and Comparative Study (Al-Qamar, 2019)
This research paper will investigate what are the common aspects of worship in Islam and Christianity and how they are practiced in modern times. The significance of this study is an Islam and Christianity are both natural and universal religion. Both religions have their own way of worship. In this paper relate the concepts of worship with respect to Islam and Christianity perspective. The purpose of this research is to explore that the Christianity has change a lot with the passage of time. Due to which the original thoughts of worship have vanished. On the other hand Islamic conceptions of worship are built on its original sources and principles even in present time. Worship is an imperative terminology. We can never be talented to recognize other religious terminologies without its sympathetic. So, I need to write this concepts of worship. Worship plays a vital role in the man’s life. Common worships in Islam and Christianity such as prayer and fasting impressed seriously and pretentious for human life. It makes the relation strong between man and Allah. It urges man to care the rights of others. When we care other’s rights our society become as an example of heave. The methodology of this study is critical and comparative.
Keywords: Islam; Christianity; worships; concepts